Alpha-Glucosidase Inhibitory Triterpene and Flavonoids Isoltaed from Prosopis africana (Fabaceae) Growing in Zangon Danborno Sabon-Gari Zaria Kaduna - Ibrahim, Abdullahi; Yusuf Mudi, Sulaiman; Abdu, Kabiru; Muhammad , Aminu; Jibril, Saidu; Dauda Mahmud, Maryam (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Powdered stem bark of Prosopis africana was extracted in ethanol and the crude ethanol extract was suspended in distilled water. The solution was partitioned sequentially in a separatory funnel with petroleum ether, chloroform and ethyl acetate hence yielding petroleum ether, chloroform, ethyl acetate and aqueous fractions respectively. The extract and fractions were evaluated for their antioxidant, and antidiabetic potentials. The EtOAc fraction displayed significant antioxidant (IC50 value of 87.06 ± 22.02 unit) and α-glucosidase (IC50 values 498.27 μg/ml) inhibition. The purification and isolation of the EtOAc fraction using column chromatography techniques lead to isolation of two compounds which were identified using (1D) (NMR) and mass spectrometry as friedelane and quercetin. The compounds were evaluated for α-glucosidase inhibition. The ccompounds showed a significant inhibitory activity against α-glucosidase with an IC50 value of 50.9 ± 0.57 µg/ml and 89.8 ± 1.9 µg/ml for friedelane and quercetin respectively. This study shows the effectiveness of P.africana stem bark extract in inhibiting α-glucosidase thereby indicating its potential as anti-hyperglycaemic agents. The obtained result supports the medicinal traditional use of this plant.